A AEROBIC EXERCISE ANALYSIS OF THE BODY IMMUNITY SYSTEM - Edina, Belva; Rahmawati, Nurul Aini (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Background : The pandemic makes people finally lazy to do activities outside the home, therefore a person's immune system can decrease. To always be healthy and fit, one of the sports that can be done is aerobics. A healthy and strong body can form antibodies faster, so that a person's immune level can increase. Objectives : To analyze the effect of aerobic exercise on the body's immune system based on empirical studies of the last 6 years. Methods and Results: Literature Review by searching previous journals or articles on two databases (Google Scholar and PubMed) published between 2014 and 2021. There were 5 journals or articles that met the inclusion criteria in the form of adolescents and adults, moderate impact aerobic exercise, improving the immune system with aerobic exercise and from 2014 to 2021. All studies stated that there was an effect of giving aerobic exercise on a person's immune system. Conclution : The effect of giving aerobic exercise on a person's immune system.